The Effect of Lecturer Commitment on Student Academic Achievement toward Student Satisfaction through Perceived Teaching Quality - Sopiah, Sopiah; Sangadji, Etta Mamang (Jurnal Ilmu Pendidikan, 2019)
The purpose of the study was to examine the direct and indirect effects of lecturer commitments to academic achievement on student satisfaction through perceived teaching quality. The population of this research is all lecturers and students in state and private universities in Indonesia. The research sample used 180 lecturers and 600 state and private university students in East Java, which were obtained by using multi-stage sampling techniques. The main findings of the study prove: 1) There is a positive and significant direct effect of lecturer commitment to academic achievement on perceived teaching quality, 2) There is a significant positive direct ef-fect of lecturer commitment to academic achievement on dental satisfaction 3) There is a significant positive direct effect of perceived teaching quality on student satisfaction, 4) There is a positive and significant indirect effect of lecture-commitment to academic achievement on student satisfaction through perceived teaching quality